Performance of endoscopic submucosal dissection for undifferentiated early gastric cancer: a multicenter retrospective cohort - Papaefthymiou, Apostolis; Kahaleh, Michel; Lemmers, Arnaud; Sferrazza, Sandro; Barret, Maximilien; Yamamoto, Katsumi; Deprez, Pierre; Marín-Gabriel, José C.; Tribonias, George; Ouyang, Hong; Barbaro, Federico; Kiosov, Oleksandr; Seewald, Stefan; Patil, Gaurav; Elkholy, Shaimaa; Coumaros, Dimitri; Vuckovic, Clemence; Banks, Matthew; Haidry, Rehan; Mavrogenis, Georgios (Endoscopy International Open, 2023)
Background and study aims Undifferentiated early gastric cancer (UD-EGC) represents an extended indication for endoscopic submucosal dissection (ESD) based on the existing guidelines. This study evaluated the prevalence of UD-EGC recurrence after ESD, and potentially implicated risk factors.Patients and methods Data from 17 centers were collected retrospectively including demographics, endoscopic and pathological findings, and follow-up data from UD-EGC cases treated by ESD. Patients with incomplete resection or advanced disease were excluded. Descriptive statistics quantified variables and calculated the incidence of recurrence. Chi-square test was applied to assess any link between independent variables and relapse; significantly associated variables were inserted to a multivariable regression model.Results Seventy-one patients were eligible, with 2:1 female to male ratio and age of 65.8 ± 11.8 years. Mean lesion size was 33.5 ± 18.8 mm and the most frequent histological subtype was signet ring-cells UGC (2:1). Patients were followed-up every 5.6 ± 3.7 months with a mean surveillance period of 29.3 ± 15.3 months until data collection. Four patients (5.6%) developed local recurrence 8.8 ± 6.5 months post-ESD, with no lymph node or distal metastases been reported. Lesion size was not associated with recurrence (P = 0.32), in contrast to lymphovascular and perineural invasion which were independently associated with local recurrence (P = 0.006 and P < 0.001, respectively).Conclusions ESD could be considered as the initial step to manage UD-EGC, providing at least an “entire-lesion” biopsy to guide therapeutic strategy. When histology confirms absence of lymphovascular and perineural invasion, this modality could be therapeutic, providing low recurrence rates.
Keywords: Endoscopy Upper GI Tract; Precancerous conditions & cancerous lesions (displasia and cancer) stomach; Endoscopy Upper GI Tract; Endoscopic resection (ESD, EMRc, ...); Endoscopy Upper GI Tract